FILM SEBAGAI PROPAGANDA DI INDONESIA - Alkhajar, Eka Nada Shofa; Yudiningrum, Firdastin Ruthnia; Sofyan, Agus (Faculty of Social Science, Universitas Negeri Semarang, 2013)
Through the study of the document as a qualitative approach, this study aims to determine how the film plays the propaganda functions from time to time, particularly from the colonial era to the New Order and know the purpose of propaganda was made.The results of this study found that the film is not a neutral medium but rather depends on the maker who uses a particular viewpoint of recording reality through the medium of film. This perspective can be injected, taped and constructed into a film in which the context is propaganda. Another fundamental findings of this study are: First, the existence of a close relationship in which the rulers (government) response to be the medium of film as a tool of propaganda with the intent and purpose of the authorities want. So it can be said that propaganda is a conscious, systematic, planned and aimed at concrete. Second, the meaning of propaganda emerging trend is always related to the purpose of the establishment the good and great â€œimageâ€ of ruler. In addition, the propaganda carried on anyway have the intention to attract the sympathy and support of the people, legitimacy, status qou or any form of distortion awareness and conduct establishment version of history â€œrulerâ€. Third, through the film we actually can know the mentality, the power relation to the identity of a nation, and the fact that the time recorded and stored in the texts of the film because the film certainly born with the socio-cultural scope or context of a particular age.